2021
DOI: 10.47391/jpma.575
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Maternal-care during labour at maternity centres of Karachi, Pakistan: Exploratory study

Abstract: Each year around 529,000 women die worldwide due to harmful consequences of childbirth in developing countries. Thus, this study aimed to explore barriers and facilitators that influence the provision of quality care during labor at maternity centers of Karachi, Pakistan. The qualitative exploratory study design was used to explore such factors from public and private maternity health facilities of Karachi, Pakistan. In-depth interviews were conducted through purposive sampling by using validated semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The findings of this study indicated that the weakness of scientific and practical capabilities of the health workforce was the second most frequent challenge in the provision of MH services. This challenge can be divided into four categories including, the negative attitude of the health workforce [ 66 , 96 ], incompetence of health professionals [ 58 , 103 ], inadequate knowledge of service providers [ 35 , 113 ], and Insufficient motivation of service providers [ 58 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study indicated that the weakness of scientific and practical capabilities of the health workforce was the second most frequent challenge in the provision of MH services. This challenge can be divided into four categories including, the negative attitude of the health workforce [ 66 , 96 ], incompetence of health professionals [ 58 , 103 ], inadequate knowledge of service providers [ 35 , 113 ], and Insufficient motivation of service providers [ 58 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Restrictions on the physical space of the services This challenge explains the barriers that limit service due to physical space issues. in this context, three categories were determined, namely limitations of service delivery space [76,93], insufficient infrastructure [24,75], and inappropriate service delivery environment [35,72].…”
Section: Fig 2 Conceptual Framework Of Evidence On Key Barriers To Th...mentioning
confidence: 99%
“…Upon thorough examination of the transcribed data, the process of coding was initiated. Coding entails the systematic reduction of the data into meaningful segments, to which labels or codes are assigned (16). This process was conducted manually, involving multiple reviews of the transcripts to identify and label segments of significance.…”
Section: Discussionmentioning
confidence: 99%
“…11 Un environnement insalubre, combiné à une absence d’équipements essentiels, de fournitures et de médicaments, compromet la qualité des soins dispensés dans les maternités et la satisfaction des parturientes. 50 , 51 Ces éléments sont en effet des facteurs prépondérants d’une expérience négative de l’accouchement. 52…”
Section: Discussionunclassified
“…11 An unhygienic environment, combined with a lack of essential equipment, supplies, and medications, compromises the quality of care in maternity units and the satisfaction of mothers. 50 , 51 These elements are indeed predominant factors of a negative childbirth experience. 52…”
Section: Discussionmentioning
confidence: 99%